Efferent pathways modulate hyperactivity in inferior colliculus - Mulders, W.H.A.M. (Soc Neuroscience, 2010)
Animal models have demonstrated that mild hearing loss caused by acoustic trauma results in spontaneous hyperactivity in the central auditory pathways. This hyperactivity has been hypothesized to be involved in the generation of tinnitus, a phantom auditory sensation. We have recently shown that such hyperactivity, recorded in the inferior colliculus, is still dependent on cochlear neural output for some time after recovery (up to 6 weeks).Wehave now studied the capacity of an intrinsic efferent system, i.e., the olivocochlear system, to alter hyperactivity. This system is known to modulate cochlear neural output. Anesthetized guinea pigs were exposed to a loud sound and after 2 or 3 weeks of recovery, single-neuron recordings in inferior colliculus were made to confirm hyperactivity. Olivocochlear axons were electrically stimulated and effects on cochlear neural output and on highly spontaneous neurons in inferior colliculus were assessed. Olivocochlear stimulation suppressed spontaneous hyperactivity in the inferior colliculus. This result is in agreement with our earlier finding that hyperactivity can be modulated by altering cochlear neural output. Interestingly, the central suppression was generally much larger and longer lasting than reported previously for primary afferents. Blockade of the intracochlear effects of olivocochlear system activation eliminated some but not all of the effects observed on spontaneous activity, suggesting also a central component to the effects of stimulation. More research is needed to investigate whether these central effects of olivocochlear efferent stimulation are due to central intrinsic circuitry or to coactivation of central efferent collaterals to the cochlear nucleus.